Racial and ethnic minority patients report different weight-related care experiences than non-Hispanic Whites - Lewis, Kristina H. (Prev Med Rep, 2016)
Our objective was to compare patients' health care experiences, related to their weight, across racial and ethnic groups. In Summer 2015, we distributed a written survey with telephone follow-up to a random sample of 5400 racially/ethnically and geographically diverse U.S. adult health plan members with overweight or obesity. The survey assessed members' perceptions of their weight-related healthcare experiences, including their perception of their primary care provider, and the type of weight management services they had been offered, or were interested in. We used multivariable multinomial logistic regression to examine the relationship between race/ethnicity and responses to questions about care experience. Overall, 2811 members (53%) responded to the survey and we included 2725 with complete data in the analysis. Mean age was 52.7 years (SD 15.0), with 61.7% female and 48.3% from minority racial/ethnic groups. Mean BMI was 37.1 kg/m(2) (SD 8.0). Most (68.2%) respondents reported having previous discussions of weight with their provider, but interest in such counseling varied by race/ethnicity. Non-Hispanic blacks were significantly less likely to frequently avoid care (for fear of discussing weight/being weighed) than whites (OR 0.49, 95% CI 0.26–0.90). Relative to whites, respondents of other race/ethnicities were more likely to want weight-related discussions with their providers. Race/ethnicity correlates with patients' perception of discussions of weight in healthcare encounters. Clinicians should capitalize on opportunities to discuss weight loss with high-risk minority patients who may desire these conversations.